The Impact On Recreational Trampling On Soil And Grass In Ciwidey Tourism Destination - Safinah Yulianty Sitania; Ricky Avenzora; Tutut Sunarminto (Media Konservasi, 2018)
The monitoring some impacts of anthropogenic applied specifically to each travel site is essential for maintaining the sustainability of the tourist activity. This study examines the effect of stamping feet of visitors to compaction of soil and the change of grass visual conditions on three conditions of different use intensity in Ciwidey. This study revealed that the trampling has effect on the penetration of the soil, groundwater levels, the changes of visual condition of the grass, and water content of the grass. The higher the intensity of land use, the higher the value of soil penetration resistance but the water content of soil and grass goes to lower. Key words: trampling effect, soil, grass, Ciwidey